Patient satisfaction with hospital care and nurses in England: an observational study - Aiken, Linda H; Sloane, Douglas M; Ball, Jane; Bruyneel, Luk; Rafferty, Anne Marie; Griffiths, Peter (BMJ open, 2018)
ObjectivesTo inform healthcare workforce policy decisions by showing how patient perceptions of hospital care are associated with confidence in nurses and doctors, nurse staffing levels and hospital work environments.DesignCross-sectional surveys of 66 348 hospital patients and 2963 inpatient nurses.SettingPatients surveyed were discharged in 2010 from 161 National Health Service (NHS) trusts in England. Inpatient nurses were surveyed in 2010 in a sample of 46 hospitals in 31 of the same 161 trusts.ParticipantsThe 2010 NHS Survey of Inpatients obtained information from 50% of all patients discharged between June and August. The 2010 RN4CAST England Nurse Survey gathered information from inpatient medical and surgical nurses.Main outcome measuresPatient ratings of their hospital care, their confidence in nurses and doctors and other indicators of their satisfaction. Missed nursing care was treated as both an outcome measure and explanatory factor.ResultsPatients’ perceptions of care are significantly eroded by lack of confidence in either nurses or doctors, and by increases in missed nursing care. The average number of types of missed care was negatively related to six of the eight outcomes—ORs ranged from 0.78 (95% CI 0.68 to 0.90) for excellent care ratings to 0.86 (95% CI 0.77 to 0.95) for medications completely explained—positively associated with higher patient-to-nurse ratios (b=0.15, 95% CI 0.10 to 0.19), and negatively associated with better work environments (b=−0.26, 95% CI −0.48 to −0.04).ConclusionsPatients’ perceptions of hospital care are strongly associated with missed nursing care, which in turn is related to poor professional nurse (RN) staffing and poor hospital work environments. Improving RN staffing in NHS hospitals holds promise for enhancing patient satisfaction.